Patience - Fiday, Beverly; Rigo, Christina Ljungren (Elgin, IL : Child's World, 1986)
Depicts times when we must exercise patience: finishing a jigsaw puzzle, waiting for our birthdays, and learning how to tie shoes.
Keywords: Patience; Patience; Conduct of life